(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Introduction: The world’s population is agiug rapidly and cancer has a high prevalence in older age, nearly 60%. There are currently over 760 million people worldwide above the age of 65 years, representing over 9% of the global population. Positron Emission Tomography-Computed Tomography (PET-CT) is a crucial imaging modality in the diagnosis, staging, and management of various malignancies, particularly in the geriatric population. At NINMAS, a year-long study was conducted to evaluate the distribution of different cancers in patients aged 65 years and above, with a focus on understanding the patterns and prevalence of malignancies in this demographic. Patients and Methods: This retrospective observational study analyzed PET-CT data of geriatric patients referred to the PET-CT division of NINMAS from January 2024 to December 2024. Data were categorized based on the type of malignancy. The proportion of cases for each type of cancer was calculated, and demographic details were analyzed to identify trends and patterns. Results: A total of 166 cases were analyzed, which represented 15.79% of total referrals. The mean age was 70.45 ± 4.67 years, and the male-to-female ratio was 2.01:1. The most common malignancy was lymphoma, accounting for 22.28%, followed by gastrointestinal (GIT) cancers (16.86%), breast cancer (13.85%), lung cancer (8.43%), female reproductive system cancers (8.43%), prostate cancer (7.83%), and head-neck cancers (7.22%). Less frequent cancers included renal carcinoma (4.81%), while cancers of unknown primary (CUP) 3.01% and urothelial cancer each comprised 2.40%. Other malignancies constituted 4.81%. A significant gender-based distribution of malignancies was observed, with lymphoma accounting for 81.08% of cases in males and breast cancer for 91.3% of cases in females. Conclusion: This study highlights the significant burden of cancer among the geriatric population, with lymphoma and gastrointestinal cancers being the most prevalent. Bangladesh J. Nuclear Med. 29(1): 13-18, 2026